Attempting to thrive during the olympic qualification window: a narrative analysis - Brown, D. J.; Wagstaff, C. R. D. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Background. The desire to succeed at the highest levels of sport has resulted in vast investment and, with it, greater scrutiny and accountability for performance. Consequently, this `need` to succeed has fostered a `win-at-all-costs` mentality and led to some environments that prioritize results and performance at the expense of athlete welfare. Although the existence of such `performance-narratives` may be prominent in elite sport, there is growing recognition that such narratives need not be at the cost of welfare, and that more should be done to create and maintain environments that promote both high performance and athlete well-being.